(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The study area is located in the southern Babylon governorate - central Iraq within longitudinal (44◦36׳- 44◦47׳) east and latitudes (32◦18׳-32◦27׳) north, within the administrative border of Hashimiya district. The study area lies on Mesopotamian plain which is characterized as a flat surface. Flow pattern map is drown by using field measurements of water levels in scattered wells over entire the region and local streams. The interflow quantity is calculated by using Darcy law after dividing the region into 7 sectors. The sectors of 1 to 6 lay north Hilla River within the selected section and the 7 lies south it. Interflow quantity of north is (0.065) m3/sec and of south is (0.0372) m3/sec. The quantity of the losing by interflow from Hilla River Channel to both sides within Hashimiya Region (along 17270m) is approximately 0.1071m3/sec in average. The losing by evaporation is 0.086m3/sec along same distance. Total sum of both losing represents 2.4% of used surface water in the region which must be added into Hilla’s share.